Correlations Between Cerebrospinal Fluid Biomarkers Concentration and Severity of Cognitive Impairment in Alzheimer Disease - Joanna Tarasiuk; Katarzyna Kapica-Topczewska; Michał Szczepański; Jan Kochanowicz; Barbara Mroczko; Alina Kułakowska (Pielęgniarstwo Neurologiczne i Neurochirurgiczne)
Introduction. Alzheimer’s disease (AD) is a progressive, neurodegenerative disease and the most common cause of dementia. Aim. The aim of the study was to assess the concentration of the 42 amino acid isoform of Aβ (Aβ1-42), Aβ1-42/Aβ1-40 (42 amino acid isoform of Aβ/40 amino acid isoform of Aβ) ratio, Tau and hyperphosphorylated Tau (pTau) protein in cerebrospinal fluid (CSF) of patients diagnosed with Alzheimer disease (AD) and to compare their correlations with degree of cognitive impairment assessed with Mini Mental State Examination (MMSE). Material and Methods. In this study, using the ELISA immunoassay standard kits, we measured the average concentration of Aβ1-42, Aβ1-42/Aβ1-40 ratio, Tau and pTau protein, in the CSF obtained from subjects diagnosed with Alzheimer’s disease (n=20, 13 women and 7 men, mean age 69.9±10.4). The cognitive functions of the patients were assessed with MMSE test. The correlations between concentration of CSF biomarkers and degree of cognitive impairment were measured using nonparametric Spearman rank correlation coefficient. Results. Our results showed negative correlation between concentration of Tau protein in CSF and the number of points scored in MMSE test (r=-0.45; p=0.046). There was no correlation between a degree of cognitive impairment assessed with MMSE test and concentration of pTau (r=-0.42; p=0.066), Aβ1-42 (r=0.02; p=0.927), and Aβ1-42/Aβ1-40 ratio (r=-0.07; p=0.775). There was also positive correlation between concentration of Aβ1-42 and Aβ1-42/Aβ1-40 ratio (r=0.91; p<0.0001), and between concentration of Tau and pTau (r=0.94; p<0.0001). Conclusions. Tau protein plays not only a crucial role in the early diagnostics, but also reflects the intensity of cognitive impairment in course of Alzheimer disease. (JNNN 2018;7(4):150–154)